Shaping Kenya County Climate Change Fund (CCCF) for resilience and peace - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
This carousel explores how climate finance can support resilience and peace through Kenya’s County Climate Change Fund. CGIAR FOCUS Climate Security, working with the ADA Consortium, shows how the CCCF helps communities manage droughts and floods while reducing climate-related tensions. Implemented in five counties, its participatory planning builds trust and compliance. CGIAR research also identifies ways to strengthen impact, including conflict-sensitive project design and greater cross-community collaboration at the landscape level.